2020
DOI: 10.21203/rs.3.rs-102838/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shallow slow earthquakes to decipher future catastrophic earthquakes in the Guerrero seismic gap.

Abstract: The Guerrero seismic gap is presumed to be a major source of seismic and tsunami hazard along the Mexican subduction zone. Until recently, there were limited observations to describe the shallow portion of the plate interface in Guerrero. For this reason, we deployed offshore instrumentation to gain new seismic data and identify the extent of the seismogenic zone inside the Guerrero gap. We discovered episodic shallow tremors and potential slow slip events which, together with repeating earthquakes, seismicity… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
4
6
0
Order By: Relevance
“…(2019) recognized NVTs activity in the southern segment of the Japan subduction zone associated to the subduction of seamounts. NVTs activity is mainly located updip of SSE and a little in zone A, similar to what has been observed recently in the Mexico subduction zone (Plata‐Martinez et al., 2021). Moreover, NVTs activity is spatially correlated with CoR subduction (Figure 2a).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(2019) recognized NVTs activity in the southern segment of the Japan subduction zone associated to the subduction of seamounts. NVTs activity is mainly located updip of SSE and a little in zone A, similar to what has been observed recently in the Mexico subduction zone (Plata‐Martinez et al., 2021). Moreover, NVTs activity is spatially correlated with CoR subduction (Figure 2a).…”
Section: Discussionsupporting
confidence: 88%
“…Plata‐Martinez et al. (2021) related the distribution of slow earthquakes in the Mexico subduction zone to the difference in relief produced by the subduction of seamounts. Therefore, we propose that the geometric heterogeneities of the seamounts of CoR could influence the diverse seismic behaviors observed in this zone.…”
Section: Discussionmentioning
confidence: 99%
“…It is consistent with the most recent inversions, where the region of maximum slip is located from 30 to 40 km depth and with a slight updip penetration in the north-west section [22,5]. Recent offshore observations showed that the mechanical properties in that segment of the subduction slab are different and it may explain the inferred updip slip [31]. Despite the similarities, it is important to mention that most of previous works are supported on constrained optimization framework and their solutions corresponds to the MAP, a different point-wise estimate than the one presented here (e.g., [4]; [5]).…”
Section: Real Case: 2006 Guerrero Slow Slip Eventsupporting
confidence: 89%
“…Tectonic tremors are slow earthquakes that are observed in the high-frequency (2-8 Hz) range (summarized in Obara & Kato, 2016). These separations of interplate regular and slow earthquakes have also been reported in various subduction zones (e.g., Dixon et al, 2014;Takemura et al, 2020;Plata-Martínez et al, 2021). Slow earthquakes tend to be concentrated in the regions with weak locking strengths (e.g., Takemura et al, 2019).…”
Section: Tectonic Interpretationssupporting
confidence: 59%